Alfalfa establishment with sorghum–sudangrass as a companion crop. Issue 1 (22nd May 2020) - La Vallie, Martina; Guretzky, John A.; Schacht, Walter H.; Redfearn, Daren D.
Abstract: Reduced first‐year yields and competition from weeds often limits alfalfa ( Medicago sativa L.) planting and establishment. This study was conducted to evaluate sorghum–sudangrass ( Sorghum bicolor  ×  S. bicolor var. sudanese ) use as a companion crop for increased forage production and weed suppression during alfalfa establishment. In 2016 and 2017, alfalfa was drill seeded in the same row with a sorghum–sudangrass companion crop (SSGCC) treatment harvested either three (2016) or two (2017) times in a Lincoln, NE, experiment. Pairing effects were compared with non‐weeded control (NWC) and weeded control (WC) alfalfa monoculture seeding treatments. Total dry matter yields in the seeding year averaged 11.73 and 2.36 Mg ha −1 in the NWC and WC treatments, respectively. The SSGCC treatment, meanwhile, increased total dry matter yields to 26.37 Mg ha −1 while reducing weed yields by 63% relative to the NWC. The increase in total dry matter yield, though, came at a cost to seeding‐year alfalfa yields, which averaged 0.19 Mg ha −1 in the SSGCC treatment, compared with 0.56 and 2.29 Mg ha −1 in the NWC and WC treatments, respectively. In spring the year after seeding, alfalfa yields averaged 4.32, 8.05, and 3.68 Mg ha −1 in the NWC, WC, and SSGCC treatments indicating that seeding with sorghum–sudangrass could be an option to increase seeding‐year forage production and establish fair‐to‐moderately productive alfalfa stands in subsequent years. Alfalfa yields in the year after seeding, though, were greatest for the WC treatment indicating presence of benefits and tradeoffs of establishment with companion crops.